Efficacy of Sanitizers on the Shelf Life of Rohu Steaks Stored at two Refrigeration Temperatures - M.R., Raghunath; C.P., Chitra; K., Ganesh; V., Vasudev; N., Sridhar; K., Hemaprasanth (Fishery Technology, 2025)
Steaks of rohu (Labeo rohita) were washed and dipped in 0, 30 and 50ppm concentrations of either Chlorine (Cl) or Chlorine dioxide (C102) for 20minJ packed in trays and stored at one of the two refrigeration temperatures; 4-6°C and 1-20C. Changes in moisture of steaks were not significant. The pH of steaks stored at both temperatures increased significantly from 6.55 to 7.37 at 4-6°C and 6.5 to 7.32 at 1-20C during storage across all treatments and especially in the last phase. Mesophilic bacteria in steaks treated with either sanitizer recorded low or nil counts initially, but quickly rebounded after 4-6 days storage at both temperatures and increased with no significant differences between treatments. Psychrophilic bacteria followed a similar pattern of increase during storage, but 50ppm C102 treated steaks had significantly lower counts than others when stored at 1-20C. Total volatile base nitrogen (TVBN) levels increased significantly at 1-2°C, but not at 4-6°C. At 1-20C, TVBN increased markedly between 8-14 days, but more slowly in C102 treated steaks. Organoleptically, the 4-60C stored steaks were inedible by the 10th day, but were still acceptable when stored at 1-20C. Sensory signs of spoilage, mainly appearance of off-odours were found to be delayed in C10 2 treated steaks at both temperatures. The lower temperature of storage for steaks appeared to be the primary cause of extension in shelf life, but C102 treatment did appear to improve the sensory properties of steaks.